Krisis Pengungsi Rohingya dan Implikasinya terhadap Stabilitas Keamanan Nasional Bangladesh - Nailah Nur Azizah; Agussalim Burhanuddin (Lembaga Pengembangan Kinerja Dosen, 2024)
The research in this journal discusses the Rohingya refugee crisis and its implications for Bangladesh's national security stability using the theory of National Security and Realism. The results using the library research method found that there were several impacts caused by Rohingya refugees, including in the fields of economy and health. The Bangladeshi government responded to the security shock by making several efforts to maintain the stability of its national security.